Doctoral theses on history of architecture in Spanish universities: a bibliometric analysis, 1977-2021 - Mochón-Bezares, Gonzalo; Sorli-Rojo, Ángela (Revista General de Información y Documentación, 2024)
This paper analyses various aspects of doctoral theses on history of architecture defended in Spanish universities between 1977 and 2021. The number of theses produced in that period was 1208, collected in the Teseo database. The temporal evolution of production, the languages used in writing, the reading universities, the production of directors and members of evaluation boards have been reviewed, paying attention to differences between genders. The results show ascending rate in production with a decrease in final years, high use of Spanish as a writing language, high production of architecture school departments, high number of academics from the Polytechnic University of Madrid, the Polytechnic University of Catalunya, the University of Seville and the Polytechnic University of Valencia among the directors and members of the tribunals. Likewise, a great gender inequality is observed in all the parameters analyzed.
Keywords: Spain; Universities; Doctoral theses; History of architecture; Bibliometrics; Scientific production